Phenylboronic acid-functionalized polyamidoamine-mediated miR-34a delivery for the treatment of gastric cancer. (5th February 2019) - Song, Zheyu; Liang, Xiao; Wang, Yudi; Han, Haobo; Yang, Jiebing; Fang, Xuedong; Li, Quanshun
Abstract : In the present research, a tumor-targeted gene carrier, PPP, was constructed through the modification of phenylboronic acid onto the surface of a polyamidoamine dendrimer, and then miR-34a delivery was employed as a model to evaluate its anti-tumor efficacy. Abstract : In the present research, a tumor-targeted gene carrier, PPP, was constructed through the modification of phenylboronic acid onto the surface of a polyamidoamine dendrimer, and then miR-34a delivery was employed as a model to evaluate its anti-tumor efficacy. The carrier PPP was identified to possess favorable miR-34a binding and condensation ability and meanwhile protect miR-34a against nuclease degradation. Through confocal laser scanning microscopy and flow cytometry analysis, PPP-mediated cellular uptake of miR-34a was found to proceed through a sialic acid-dependent endocytosis pathway and the nanoparticles could achieve endosome/lysosome escape within 6 h. Further, an anti-proliferative effect could be obtained after PPP/miR-34a transfection through the induction of cell apoptosis. Meanwhile, the inhibition of migration and invasion could be realized through blocking the Notch-1 signaling pathway after PPP/miR-34a treatment. Finally, PPP possessed acceptable safety and inhibited in vivo tumor growth through the in situ apoptosis of tumor sites, which relied on the specific tumor-targeting ability and long circulation time in the blood. In summary, the derivative PPP could be potentially utilized as an efficient carrier for miR-34a delivery to achieve an anti-tumor response in clinical use.